Pengembangan LKPD Berbasis Pola Argumentasi Toulmin untuk Meningkatkan Keterampilan Argumentasi Peserta Didik pada Materi Hidrolisis Garam - Setyorini, Ratna Dwi; Rusmini (UNIB Press, 2025)
This research aimed to develop LKPD based on Toulmin's argumentation pattern to improve students' argumentation skills on salt hydrolysis material. salt hydrolysis material. The feasibility of LKPD based on Toulmin's argumentation pattern is reviewed from the validity, practicality, and effectiveness. validity, practicality, and effectiveness. This research referred to the 4D design with three stages 4D design with three stages, namely defining, designing, and developing. The limited trial was conducted in class XII-4 SMAN 16 Surabaya. The results obtained include (1) The mode score for content and construct validity is ≥ 4, which is included in the valid category; (2) the mode of learner responses category is excellent; (3) the mode of learner activities and learning implementation are included in the excellent category; (4) the results of the normality test show the normality test results show a P-value> 0.100, which means it is greater than the error rate (α) of 0.100. greater than the error rate (α) of 0.05, so that the data is normally distributed; and (5) the results of the paired normal distribution; and (5) the paired sample t-test results show a P-value of of 0.000, which is smaller than than 0.05 so that H₀ is rejected and Ha is accepted. Thus, there is an increase in students' argumentation skills after the use of LKPD based on Toulmin's argumentation pattern.